Professional burnout in European young oncologists: results of the European Society for Medical Oncology (ESMO) Young Oncologists Committee Burnout Survey - (:unkn) unknown (OXFORD UNIV PRESS, 2017)
Background: Burnout in health care professionals could have serious negative consequences on quality of patient care, professional satisfaction and personal life. Our aim was to investigate the burnout prevalence, work and lifestyle factors potentially affecting burnout amongst European oncologists <= 40 (YOs). Methods: A survey was conducted using the validated Maslach Burnout Inventory (MBI) and additional questions exploring work/lifestyle factors. Statistical analyses were carried out to identify factors associated with burnout. Results: Total of 737 surveys (all ages) were collected from 41 European countries. Countries were divided into six regions. Results from 595 (81%) YOs were included (81% medical oncologists; 52% trainees, 62% women). Seventy-one percent of YOs showed evidence of burnout (burnout subdomains: depersonalization 50%; emotional exhaustion 45; low accomplishment 35%). Twenty-two percent requested support for burnout during training and 74% reported no hospital access to support services. Burnout rates were significantly different across Europe (P<0.0001). Burnout was highest in central European (84%) and lowest in Northern Europe (52%). Depersonalization scores were higher in men compared with women (60% versus 45% P = 0.0001) and low accomplishment was highest in the 26-30 age group (P<0.01). In multivariable linear regression analyses, European region, work/life balance, access to support services, living alone and inadequate vacation time remained independent burnout factors (P<0.05). Conclusions: This is the largest burnout survey in European Young Oncologists. Burnout is common amongst YOs and rates vary across Europe. Achieving a good work/life balance, access to support services and adequate vacation time may reduce burnout levels. Raising awareness, support and interventional research are needed.
Keywords: burnout; work-life balance; young oncologists; European; WORK-LIFE BALANCE; AMERICAN SURGEONS; US ONCOLOGISTS; SATISFACTION; PHYSICIANS; CAREER; POPULATION; PREVALENCE; STUDENTS; PLANS